The Work-Related Basic Need Satisfaction Scale: An Italian Validation - Colledani, Daiana; Capozza, Dora; Falvo, Rossella; Di Bernardo, Gian Antonio (Frontiers in Psychology, 2018)
The aim of the present study was twofold: validating the Work-related Basic Need Satisfaction (W-BNS) scale in the Italian social context, and exploring the mediational role of organizational commitment in the relationship between basic needs and two job-attitude indicators (i.e., turnover intentions and job satisfaction). Three studies were carried out. Study 1 was conducted on two samples of employees. Exploratory factor analysis and parallel analysis were run on the first sample, while confirmatory factor analyses were run on the second. Results supported the three-dimensional structure of the W-BNS scale. Study 2 was conducted on a third sample of employees. Results supported the construct validity of the scale, by showing that needs for competence, autonomy, and relatedness were associated with job resources (social support, job autonomy, professional growth), low burnout, and job attitudes (job satisfaction, turnover intentions, commitment). In addition, results showed that responses to the scale are not affected by social desirability. Study 3 was conducted on a sample obtained by grouping together all respondents from Studies 1 and 2. A model was tested to investigate the mediating role of commitment in the relationship between the three needs and job attitudes. Organizational commitment was measured by using the Klein et al., Unidimensional, Target-free scale (the KUT). Results supported the nomological validity of the scale. In line with our expectations, the three needs were associated with organizational commitment, which mediated the effects of basic needs on job attitudes. Practical implications of findings and directions for future research are discussed.